Climate change, human mobility, and peace and security: An examination of dominant policy narratives (Burkina Faso) - Schapendonk, Frans; Ramos, Cristina; Scartozzi, Cesare Marco; Cisse, Ramatoulaye; Laderach, Peter; Pacillo, Grazia (2025)
This automated content analysis report assesses the current ‘state of play’ of Burkina Faso’s policy discourse with regards to the intersection of climate change, human mobility, and conflict and fragility. We find that mobility, in various forms, is recognised as a pressing issue in nearly all policy sectors. However, the depth and nature of this engagement differ significantly across sectors, with various discourses adopting differing discursive framings depending on sectoral priorities. We identify three main overarching challenges with regards to mainstreaming a coherent discursive framing within Burkinabe policy discourses. These include, firstly, the negative framing of pastoralist systems and a push for sedentarisation, which risks undermining the resilience and traditional knowledge systems of such communities and potentially contribute to further marginalisation. Secondly, we detect an absence of effective engagement with the climate mobility nexus within gender-specific policy sectors, and a broader failure to recognize ethnic dimensions with Burkina Faso’s current displacement risk landscape. Lastly, whilst some recognition of the role of climate change is evident, climate-related impacts are largely framed in a securitised manner, hindering the recognition and development of environmental peacebuilding opportunities.